Pelatihan Aplikasi Microsoft Word Pada Data Informasi Di Dinas Sosial Kabupaten Batubara - Zulfi Azhar; Jeperson Hutahaean; Neni Mulyani (Jurnal TUNAS, 2022)
Employees of the Batubara District Social Service are not familiar with the many facilities provided in the Microsoft Word software. Because so far they have not been provided with direct training for the introduction of these functions. To need encouragement to improve the ability to operate office software, especially Microsoft Word software in processing information data. This community service activity aims to improve the ability of Social Service Employees to use Microsoft Office properly and improve skills in performing services and work in their workplace. The training method is by means of discussion and interactive in conveying knowledge to training participants. This activity uses knowledge in theory and practice in the classroom. The success of this training activity is measured by measuring the results of the participant's assessment through a written test. This training provides knowledge that can be implemented in the trainees' workplaces. Knowledge of this application is expected to contribute to improving the ability of information data which is very helpful in completing tasks in the agency. The results of the assessment in participating in this training used pretest and posttest tests. The participants were able to understand the training material based on the results of the pretest scores with an average score of 57.5 and posttest results with an average score of 87.5.